The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1001/jamanetworkopen.2022.31963
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pharmacologic Treatment of Heart Failure With Preserved and Mildly Reduced Ejection Fraction

Abstract: ImportanceIn recent years, significant progress has been made in the pharmacologic treatment of heart failure (HF) with reduced ejection fraction (HFrEF), but there is still insufficient evidence for drug therapy for HF with preserved ejection fraction (HFpEF) and mildly reduced ejection fraction (HFmrEF).ObjectiveTo compare the outcomes associated with different drug combinations for the treatment of HFpEF and HFmrEF.Data SourcesA search of the PubMed, Embase, and Cochrane Central Register of Controlled Trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 28 publications
(63 reference statements)
0
10
0
Order By: Relevance
“…Also, a meta-analysis showed no benefit in the risk of all-cause mortality or cardiovascular death for six therapeutic drugs, including SGLT2i, ARNI and mineralcorticoid receptor antagonist (MRA). Compared with placebo, SGLT2i, ARNI and MRA were related to the significant reduction of HF hospitalization risk, among which SGLT2i had the most significant effect (Xiang et al, 2022). Moreover, the results of the DELIVER study demonstrated that dagliflozin reduces the risk of cardiovascular death or worsening heart failure in HFpEF patients independent of baseline renal function (Solomon et al, 2022), our study also included patients with eGFR< 30 ml/min/1.73 m 2 , and confirmed the consistency of the efficacy of spironolactone in this population, further demonstrating the benefit of spironolactone in patients with HFpEF and CKD.…”
Section: Discussionmentioning
confidence: 90%
“…Also, a meta-analysis showed no benefit in the risk of all-cause mortality or cardiovascular death for six therapeutic drugs, including SGLT2i, ARNI and mineralcorticoid receptor antagonist (MRA). Compared with placebo, SGLT2i, ARNI and MRA were related to the significant reduction of HF hospitalization risk, among which SGLT2i had the most significant effect (Xiang et al, 2022). Moreover, the results of the DELIVER study demonstrated that dagliflozin reduces the risk of cardiovascular death or worsening heart failure in HFpEF patients independent of baseline renal function (Solomon et al, 2022), our study also included patients with eGFR< 30 ml/min/1.73 m 2 , and confirmed the consistency of the efficacy of spironolactone in this population, further demonstrating the benefit of spironolactone in patients with HFpEF and CKD.…”
Section: Discussionmentioning
confidence: 90%
“…SGLT2 inhibitors are therefore recommended for all patients with HFmrEF. A recent meta-analysis of studies on the management of HF with mildly reduced or preserved ejection fraction (EF>40%) confirmed that SGLT2 inhibitors are currently the optimal drug class for these patients [ 132 ]. Overall evidence suggests a potential accumulative improvement in HF hospitalization rather than all-cause death with the combination of SGLT2 inhibitors with an ACEi/ARB/ARNI, an MRA or a beta blocker [ 132 , 133 ].…”
Section: Chronic Heart Failurementioning
confidence: 99%
“…A recent meta-analysis of studies on the management of HF with mildly reduced or preserved ejection fraction (EF>40%) confirmed that SGLT2 inhibitors are currently the optimal drug class for these patients [ 132 ]. Overall evidence suggests a potential accumulative improvement in HF hospitalization rather than all-cause death with the combination of SGLT2 inhibitors with an ACEi/ARB/ARNI, an MRA or a beta blocker [ 132 , 133 ]. However, RAASi through ACEi, ARB or ARNI has not yet been specifically investigated among patients with HFmrEF in a RCT and current evidence for their use remains limited.…”
Section: Chronic Heart Failurementioning
confidence: 99%
See 1 more Smart Citation
“…3 In addition, a recent meta-analysis found that sacubitril/valsartan was associated with a significant reduction in the risk of HF hospitalization in patients with HFpEF when compared to placebo. 4 Therefore, the AHA/ACC/HFSA Guideline will be updated in 2022 to recommend sacubitril/valsartan treatment for patients with HFpEF as a class IIb indication. 5 Sacubitril/valsartan is started at a low dose and up-titrated to the target dose with consideration of safety and tolerability.…”
Section: Introductionmentioning
confidence: 99%